University College of Pharmaceutical Sciences, Kakatiya University, Warangal, Telangana State - 506009, India - Parimala Devi; Aravindhan V; Narmatha Bai V; Rajendran A (International Journal of Phytomedicine, 2015)
In the present investigation, diversity of orchids in Anamalai hill range was studied which recorded 20 genera with 25 species with their medicinal importance. The study observed the rapid depletion of orchid species due to destruction of natural habitat by deforestation, upper layer soil erosion, overgrazing, etc. Their disappearance indicates a change in the quality of soil and air of the region. Therefore, adequate management actions including both in situ and ex situ conservation measures need to be undertaken.